2016
DOI: 10.1007/s00005-015-0382-6
|View full text |Cite
|
Sign up to set email alerts
|

Novel Insights into the Roles of Rho Kinase in Cancer

Abstract: Rho-associated coiled-coil kinase (ROCK) is a major downstream effector of the small GTPase RhoA. The ROCK family, consisting of ROCK1 and ROCK2, plays a central role in the organization of the actin cytoskeleton, and is involved in a wide range of fundamental cellular functions such as contraction, adhesion, migration, proliferation, and apoptosis. Since the discovery of effective inhibitors such as fasudil and Y27632, the biological roles of ROCK have been extensively explored in numerous diseases, including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
134
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 174 publications
(145 citation statements)
references
References 242 publications
(334 reference statements)
6
134
1
Order By: Relevance
“…Rho‐associated protein kinase (ROCK), a serine‐threonine kinase belonging to the AGC (PKA/PKG/PKC) family, regulates cell shape and migration by acting on the cytoskeleton; it also plays an important role in modulating cell survival, proliferation and apoptosis through multiple downstream targets . The 2 known mammalian ROCK isoforms, ROCK1 and ROCK2, are 62% homologous overall and 92% homologous in their kinase domain . Because ROCK affects multiple biological processes, ROCK inhibitors have been tested for clinical effects, including on cancer .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Rho‐associated protein kinase (ROCK), a serine‐threonine kinase belonging to the AGC (PKA/PKG/PKC) family, regulates cell shape and migration by acting on the cytoskeleton; it also plays an important role in modulating cell survival, proliferation and apoptosis through multiple downstream targets . The 2 known mammalian ROCK isoforms, ROCK1 and ROCK2, are 62% homologous overall and 92% homologous in their kinase domain . Because ROCK affects multiple biological processes, ROCK inhibitors have been tested for clinical effects, including on cancer .…”
Section: Introductionmentioning
confidence: 99%
“…Because ROCK affects multiple biological processes, ROCK inhibitors have been tested for clinical effects, including on cancer . The ROCK inhibitor Fasudil was approved for clinical treatment of cerebral vasospasm in Japan and China . Y‐27632, another well‐established ROCK inhibitor, has been widely used to study the biological and pharmacological functions of ROCK in vitro and in vivo .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“… showed that ROCK activation in mouse pancreatic ductal adenocarcinoma cells increased their invasive growth into a three‐dimensional collagen matrix by extensive induction of matrix metalloproteinases and increased matrix remodeling. These findings combined together suggest that Rho‐ROCK signaling is not the primary cause but critical for several important phenotypes of cancer, which may be exploited therapeutically in combination with other anticancer therapies .…”
Section: Rho Signaling Research In Current Statusmentioning
confidence: 98%